ASSERTIVE COMMUNICATION AND STRESS LEVEL AMONG FAMILIES LIVING WITH PULMONARY TUBERCULOSIS PATIENTS - Eko Mulyadi; Moh. Arroyhan; Abd Wahid (Universitas Airlangga, 2025)
BackgroundFamilies play a pivotal role in supporting the recovery of patients with pulmonary tuberculosis (TB); however, this role is frequently accompanied by high psychological stress. This study aimed to examine the relationship between assertive communication and stress levels among families caring for pulmonary TB patients.MethodsThis analytical observational study employed a cross-sectional design. A total of 71 family members of TB patients were selected using a simple random sampling technique. Data were analyzed using the Spearman Rank correlation test with a significance level of α = 0.01.ResultsFindings indicated that 50.8% of participants demonstrated moderate assertive communication, while 42.6% experienced mild stress levels. Statistical analysis revealed a significant correlation between assertive communication and stress levels (ρ = 0.005), indicating that higher assertive communication skills are associated with lower stress levels.ConclusionAssertive communication plays a vital role in mitigating stress among families of TB patients. Strengthening family assertiveness through psychoeducation and counseling interventions could enhance coping abilities and improve overall family well-being.